2004
DOI: 10.1097/01.tp.0000144055.78462.4f
|View full text |Cite
|
Sign up to set email alerts
|

Recipient-Derived Hepatocytes in Sex-Mismatched Liver Allografts after Liver Transplantation: Early versus Late Transplant Biopsies

Abstract: Some hepatocytes of sex-mismatched liver grafts were replaced by "recipient-derived cells" during injury. Such repopulation is more common in the early liver-graft biopsies. The severity of acute cellular rejection appears to have no effect on the rate of recipient-derived repopulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 20 publications
1
32
3
Order By: Relevance
“…Although FISH analysis was performed in only one FAP patient, the presence of recipient-derived cells was also confirmed with almost the equal frequency of previous reports in other diseases. 21,22 However, despite the presence of recipient-derived cells, our results showed that ATTR mRNA was not expressed in the transplanted liver and serum ATTR could not be detected. Previous studies reported that hepatocyte transdifferentiation from recipient bone marrow stem cells was rare, 27 -30 suggesting that the recipient-derived cells in the transplanted liver may be too immature to synthesize TTR.…”
Section: Discussioncontrasting
confidence: 77%
“…Although FISH analysis was performed in only one FAP patient, the presence of recipient-derived cells was also confirmed with almost the equal frequency of previous reports in other diseases. 21,22 However, despite the presence of recipient-derived cells, our results showed that ATTR mRNA was not expressed in the transplanted liver and serum ATTR could not be detected. Previous studies reported that hepatocyte transdifferentiation from recipient bone marrow stem cells was rare, 27 -30 suggesting that the recipient-derived cells in the transplanted liver may be too immature to synthesize TTR.…”
Section: Discussioncontrasting
confidence: 77%
“…Observations from the human liver allotransplantation indicate that cells of recipient origin can replace biliary epithelial cells, endothelial cells, and hepatocytes, this is consistent with the concept that circulating pluripotent progenitor cells exist and are capable of differentiating into endothelial cells, epithelial cells, and hepatocytes [110][111][112][113]. In bone marrow allotransplantation for haematological malignancy, the bone marrow was from hepatitis B immune donors, it was shown that chronic hepatitis B infection in recipients was eradicated through the adoptive transfer of hepatitis B core antigen reactive CD4+ T cell subsets [114].…”
Section: Human Studiessupporting
confidence: 74%
“…Our researchers previously demonstrated that a Lewis-to-DA rat liver graft becomes a host-donor chimera via recipient stem cell repopulation and is accepted without immunosuppression (18). This repopulation process has been reported to occur to a meager extent after the transplantation of a variety of organ types in humans (19)(20)(21)(22)(23)(24) but is inefficient, perhaps due to the provision of conventional immunosuppression, which acts to eliminate donor-recipient interactions and retards liver regeneration in animals (18). Recently, Fan et al confirmed these findings.…”
Section: Introductionmentioning
confidence: 99%